2004
DOI: 10.1111/j.1365-2605.2004.00476.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of reactive oxygen species and apoptosis in the pathogenesis of varicocele in a rat model and efficiency of vitamin E treatment

Abstract: We investigated role of reactive oxygen species (ROS) and apoptosis in the pathogenesis of infertility in experimental model of varicocele. The protective effect of vitamin E was also examined. Three groups of rats were constructed as the first group had sham operation, experimental varicoceles were established by partial ligation of the left renal vein in later two groups. Third group had received vitamin E. Production of ROS was determined by chemiluminescence assay (CL). The in situ end labelling technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 28 publications
0
42
0
2
Order By: Relevance
“…Research conducted during the last decade has provided growing support to the concept that oxidative stress (OS) is one of the main causes of male infertility. Reactive oxygen species may also act through induction of apoptosis [12]. Turkyilman et al implicated that elevated nitric oxide (NO) may be another mechanism of injury in varicoceles, independent of other free radicals [13].…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted during the last decade has provided growing support to the concept that oxidative stress (OS) is one of the main causes of male infertility. Reactive oxygen species may also act through induction of apoptosis [12]. Turkyilman et al implicated that elevated nitric oxide (NO) may be another mechanism of injury in varicoceles, independent of other free radicals [13].…”
Section: Discussionmentioning
confidence: 99%
“…Many natural antioxidants can be effectively applied to eliminate oxidative stress by reducing the level of testicular-free radicals, including vitamin E (Cam et al, 2004), vitamin C, L-cysteine, and diphenyl-phenylene-diamine (Ahmed et al, 2011). In this study, we used tBHQ, which is not only a direct antioxidant used to preserve various oils, fats, and food by inhibiting autopolymerization of organic peroxides (de Guzman et al, 2009), but is also an indirect antioxidant acting as a nuclear factor erythroid 2-related factor 2 activator (Nrf2) to promote its accumulation in the nucleus and up-regulating the expression of antioxidant genes against oxidative stress (Cheung et al, 2011;Saykally et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It may also induce spontaneous death of mature sperms. Cam et al [32] and Barqawi et al [33] in their experimental rat model studies of varicocele found an increased rate of apoptosis in varicocele group, when compared to the sham surgery group. This apoptosis may be ROS mediated, and could be reversed through the use of antioxidants (i.e.…”
Section: Pathophysiology Of Varicocelementioning
confidence: 99%